The Ubiquitin‐proteasome pathway regulates Nectin2/CD112 expression and impairs NK cell recognition and killing. Issue 6 (27th March 2019) - Molfetta, Rosa; Milito, Nadia D.; Zitti, Beatrice; Lecce, Mario; Fionda, Cinzia; Cippitelli, Marco; Santoni, Angela; Paolini, Rossella
Abstract: Nectin2 is a member of immunoglobulin‐like cell adhesion molecules and plays a prominent role in the establishment of adherens and tight junctions. It is also upregulated on the surface of tumor and virus‐infected cells where it functions as a ligand for the activating receptor CD226, thus contributing to cytotoxic lymphocyte‐mediated recognition and killing of damaged cells. Little is currently known about the regulation of Nectin2 expression and, in particular, whether posttranscriptional and posttranslational mechanisms are involved. Here, we analyzed Nectin2 expression on a panel of human tumor cell lines and primary cultures and we found that Nectin2 is mainly expressed in cytoplasmic pools. Moreover, we demonstrated that ubiquitination of Nectin2 promotes its degradation and is responsible for protein intracellular retention. Indeed, inhibition of the ubiquitin pathway results in increased Nectin2 surface expression and enhances tumor cell susceptibility to NK cell cytotoxicity. Our results demonstrate a previously unknown mechanism of Nectin2 regulation revealing that the ubiquitin pathway represents a potential target of intervention in order to increase susceptibility to NK cell‐mediated lysis. Abstract : The ubiquitin pathway negatively regulates surface expression of Nectin2, a ligand for the activating NK‐cell receptor CD226. The neo‐synthetized Nectin2 is ubiquitinated before reaching the plasma membrane and either subjected to proteasomal degradation or retained intracellularly. In healthy cells, limiting Nectin2 membrane expression may avoid a potential aberrant NK‐cell activation, while in transformed cells may represent a mechanism to evade NK‐cell surveillance.